The Mutual Inhibition of FoxO1 and SREBP-1c Regulated the Progression of Hepatoblastoma by Regulating Fatty Acid Metabolism - Yu Hu; Hongyan Zai; Wei Jiang; Zhenglin Ou; Yuanbing Yao; Qin Zhu (Mediators of Inflammation)
Background. Hepatoblastoma (HB) is the most common liver malignancy in pediatrics, but the treatment for this disease is minimal. This study is aimed at exploring the effect of FoxO1 and SREBP-1c on HB and their mechanism. Methods. FoxO1, SREBP-1c, FASN, ACLY, ACC, and MAGL expressions in tissue samples were detected by RT-qPCR and WB. IHC was utilized to measure FASN content. Overexpression and knockdown of FoxO1 and sSREBP-1c were performed on Huh-6 cells. Cell proliferation, migration, and invasion were examined by CCK8, scratch, and transwell assay. ELISA was performed to test the ATP, FAO, NEFA, and Acetyl-CoA contents. ChIP was used to detect the interaction between SREBP-1c protein and the FoxO1 gene. In vivo tumorigenesis was conducted on mice. The morphology of tumor tissue sections was observed by HE staining. Results. FoxO1 expression was downregulated in HB tissue, while the expressions of SREBP-1c, FASN, ACLY, ACC, and MAGL were upregulated. In Huh-6 cells and mouse tumor tissues, FoxO1 knockdown resulted in increased cell proliferation, migration, and invasion and active fatty acid metabolism. On the contrary, after the knockdown of SREBP-1c, cell proliferation, migration, and invasion were weakened, and fatty acid metabolism was significantly reduced. SREBP-1c interacted with the promoter of the FoxO1 gene. When FoxO1 was knocked down, the tumor tissue was more closely packed. After the knockdown of the SREBP-1c gene, the structure of tumor cells was deformed. Conclusion. FoxO1 and SREBP-1c inhibited each other in HB, leading to the increase of intracellular fatty acid metabolism, and ultimately facilitated the development of HB.